Southern craft food diversity : challenging the myth of a US food revival - Byrd, Kaitland M. (Sociology of diversity., 2021)
"Driven by consumers' desire for slow and local food, craft breweries, traditional butchers, cheese makers and bakeries have been popping up across the US in the last twenty years. Typically urban and staffed predominantly by white middle class men, these industries are perceived as a departure from tradition and mainstream lifestyles. But this image obscures the diverse communities that have supported artisanal foods for centuries. Using the oral histories of over 100 people, this book brings to light the voices, experiences, and histories of marginalized groups who keep Southern foodways alive. The larger than life stories of these individuals reveal the complex reality behind the movement and show how they are the backbone of the so-called new explosion of craft food"--